Influence of magnetic field on optical response in a degenerate four-level lambda-type atomic system - Thuy Tram, Nguyen; Thi Phuong Anh, Nguyen; Thi Ngoc, Nguyen; Thi Ngoc Yen, Hoang; Thi Thao, Cao; Nga, Luong Thi Yen; Hai Quang, Ho; Le Van, Doai; Nguyen, Thi Kieu Oanh (Communications in Physics, 2026)
We theoretically investigate the optical response of a degenerate four-level \(Λ\)-type atomic system under the influence of an external magnetic field. The applied magnetic field lifts the degeneracy of the ground sublevels via the Zeeman effect, thereby altering the two-photon resonance conditions for electromagnetically induced transparency (EIT) formation and causing the atomic response to evolve from single-EIT to double-EIT, accompanied by shifts in the EIT positions. Such variations in the EIT positions result in corresponding changes in the dispersion and group index curves, allowing the selection of desired frequency regions for different response regimes. As a result, the system can switch between transparency and absorption, as well as between slow and fast light. These findings highlight the feasibility of controlling light propagation via magnetic field, with potential applications in optical switching and quantum information technologies.